Enforcement of Post-Divorce Financial Obligations in Indonesian Islamic Family Law: A Case Study of Child Maintenance - Haris Muizzuddin, Ahmad (Berasan: Journal of Islamic Civil Law, 2025)
This study examines the enforcement of post-divorce financial obligations in Indonesian Islamic family law, with a particular focus on child maintenance. The research aims to analyse how the Religious Courts implement judicial decisions related to child support after divorce and to identify the challenges faced in ensuring compliance. Employing a normative juridical approach complemented by empirical data, the study draws upon statutory provisions, classical fiqh literature, and fieldwork consisting of interviews with judges and court officials in Bengkulu. The findings reveal that although Indonesian legislation and the Compilation of Islamic Law explicitly require fathers to provide child maintenance following divorce, enforcement remains problematic. The main obstacles include the limited legal instruments available to compel execution, the passive role of the courts that rely on the mother's initiative to file for execution, and the low level of legal awareness among litigants. The case analysis of Decision No. 174/Pdt.G/2012/PA Bn illustrates these structural and procedural weaknesses. The study concludes that effective protection of children's rights requires strengthening the execution mechanisms of the Religious Courts, enhancing public legal literacy, and reformulating policies that align with both Islamic legal principles and the demands of contemporary justice.